2018
DOI: 10.3389/fphys.2018.01482
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic Substrates for Atrial Fibrillation in Obesity

Abstract: Global obesity rates have nearly tripled since 1975. This obesity rate increase is mirrored by increases in atrial fibrillation (AF) that now impacts nearly 10% of Americans over the age of 65. Numerous epidemiologic studies have linked incidence of AF and obesity and other obesity-related diseases, including hypertension and diabetes. Due to the wealth of epidemiologic data linking AF with obesity-related disease, mechanisms of AF pathogenesis in the context of obesity are an area of ongoing investigation. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 152 publications
(207 reference statements)
0
26
0
6
Order By: Relevance
“…RA pressure or volume overload could stimulate the remodeling process resulting in fibrosis development. Myocardial fibrosis plays a key role in POAF development . AF might develop after percutaneous patent foramen ovale closure, and in relation with the progression of the remodeling process …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RA pressure or volume overload could stimulate the remodeling process resulting in fibrosis development. Myocardial fibrosis plays a key role in POAF development . AF might develop after percutaneous patent foramen ovale closure, and in relation with the progression of the remodeling process …”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic system activation may also be associated with POAF development, which has been reported to be reduced by the use of beta‐blockers before the procedure. Many associated predictors such as left atrial (LA) volume, LV ejection fraction, or left ventricular global longitudinal strain (LVGLS) have thus been described, and can be measured by echocardiography before the procedure …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that aging and obesity are two of the most prominent risk factors for AF occurrence [5][6][7]. In obesity, cardiometabolic changes in the heart favor reactive oxygen species (ROS) production [8,9]. Oxidative stress activates calmodulin-dependent protein kinase II (CaMKII), leading to arrhythmogenic hyperphosphorylation of RyR2.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial structural remodeling is a prominent feature of AF and contributes to altered conduction 36,37 . We therefore examined atrial myocyte apoptosis by means of terminal deoxyribonucleotidyl transferase (TdT)-mediated biotin-16-deoxyuridine triphosphate (dUTP) nick-end labeling (TUNEL) staining (Fig.…”
Section: Effects Of Bo On Fibrosis and Myocyte Apoptosis In Atriummentioning
confidence: 99%